2018
DOI: 10.1073/pnas.1718987115
|View full text |Cite
|
Sign up to set email alerts
|

Selective visual representation of letters and words in the left ventral occipito-temporal cortex with intracerebral recordings

Abstract: We report a comprehensive cartography of selective responses to visual letters and words in the human ventral occipito-temporal cortex (VOTC) with direct neural recordings, clarifying key aspects of the neural basis of reading. Intracerebral recordings were performed in a large group of patients ( = 37) presented with visual words inserted periodically in rapid sequences of pseudofonts, nonwords, or pseudowords, enabling classification of responses at three levels of word processing: letter, prelexical, and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 47 publications
9
123
0
1
Order By: Relevance
“…However, a recent intracranial study also detected visual-word responses in the medial FG/CoS (Lochy et al, 2018). The words used in this study were high-frequency nouns.…”
Section: Figurementioning
confidence: 51%
See 1 more Smart Citation
“…However, a recent intracranial study also detected visual-word responses in the medial FG/CoS (Lochy et al, 2018). The words used in this study were high-frequency nouns.…”
Section: Figurementioning
confidence: 51%
“…In an intracranial study, evidence was found for Letter representations stretching from the Inferior Occipital Gyrus to the amLOC region (Lochy et al, 2018). Due to the presence of anterior Letter representations, the authors concluded that visual word recognition is not hierarchical.…”
Section: Reading Acquisitionmentioning
confidence: 97%
“…Nevertheless, the functional posterior-to-anterior hierarchy in the left VOTC has recently been challenged. In a very recent work, Lochy and colleagues 58 report an extensive functional mapping of the VOTC for selective responses to visual letter strings and words with intracerebral recordings. Besides showing letter-selective responses across all the VOTC, they found responses to real words in a region extending more anteriorly than the VWFA.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is important to point out that our findings shedding light on the left ventral ATL do not preclude a similar involvement of its right hemispheric counterpart, which was not explored in SEEG in the present study. We therefore emphasize again the need for additional intracerebral recordings in larger samples of participants [80,81] in the bilateral ventral ATL in order to clarify its role in crossmodal person-related processing. In addition, recording of electrical activity of individual neurons [82] in the human ATL may provide more direct evidence for integration of identity-related faces and names at the neuronal level and provide useful contrasting information with previously recorded responses in the MTL [24].…”
Section: The Role Of the (Left) Atlmentioning
confidence: 90%